Cosmic Transmission of Periodontal, Cardiovascular and Kidney Disease via Nanobacteria - Jafar Kolahi (Wolters Kluwer Medknow Publications, 2011)
Introduction: Nanobacteria (NB) are mysterious particles that have spurred one of the biggest controversies in modern micro-biology. NB has been reported to be present in animal and human blood, tissue culture cell lines, wastewater and etc. NB appear to cause or contribute to common diseases of the mankind e.g. periodontitis, formation of kidney stone, heart calcifications, coronary artery calcification, atherosclerotic plaque. Recent data on the far-ultraviolet extinction of starlight in our galaxy and in external galaxies is interpreted in terms of the widespread occurrence of organic particles of optical refractive index 1.4 and radii less than or equal to 20 nm. Such particles are candidates for NB such as recently been found in abundance on the Earth. Unbelievably nanobacteria-like rods observed at the surface of the Tataouine meteorite and Martian rock.The hypothesis: It seems logic to hypothesize that aliens from inner space, nanobacteria, can bring us new disease such as periodontal, cardiovascular and kidney diseases via space travels or meteorites or interstellar dusts.Evaluation of the hypothesis: The main criticism with this idea is how NB can keep alive during transfer among seriously life threatening condition in interstellar space. NB are generally thought to be very difficult to deactivation, exceptionally resistant to heat, are not deactivated by physical or chemical treatments including autoclaving, UV treatment, and various biocides. Health care providers, health policy makers and space agencies e.g. NASA and European Space Agency should make a concentrated effort to prevent transmission of NB especially following space travels.